2017
DOI: 10.1111/1747-0080.12367
|View full text |Cite
|
Sign up to set email alerts
|

Protein supplements and adolescent athletes: A pilot study investigating the risk knowledge, motivations and prevalence of use

Abstract: The evident lack of knowledge regarding protein supplements demonstrates a necessity for further education of athletes, coaches and families regarding the responsible purchasing and use of protein supplements in the current landscape of sports nutrition. Future research should further explore the role of the Internet in protein supplement purchase and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 28 publications
3
22
2
2
Order By: Relevance
“…, In most cases, supplements are unnecessary. A recent paper from Australia described protein supplement use in 60% of the adolescents who participated . Counseling on how to use food to maximize training adaptions is essential.…”
Section: The Impact Of Exercise On Blood Glucose Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…, In most cases, supplements are unnecessary. A recent paper from Australia described protein supplement use in 60% of the adolescents who participated . Counseling on how to use food to maximize training adaptions is essential.…”
Section: The Impact Of Exercise On Blood Glucose Levelsmentioning
confidence: 99%
“…A recent paper from Australia described protein supplement use in 60% of the adolescents who participated. 77 Counseling on how to use food to maximize training adaptions is essential. Advice on the risks of supplement use, which include contamination with banned performance-enhancing substances should be provided along with guidance on anti-doping according to the sport and level of competition, as some sports begin anti-doping procedures below the age of 18 years.…”
Section: Supplementsmentioning
confidence: 99%
“…The Asia-Pacific region, including Australia, has been identified as the area in which the fastest growth is expected, due to a focus on leading active and healthy lifestyles [3]. Muscle building supplements are widely available and yet they are poorly regulated [4], contributing to easy access, including by adolescents. These conditions contribute to high potential harm for adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Protein shakes and powders were reportedly used by 34.8% of high school adolescent boys in the US [14], and 25% of adolescent boys in Australia [15]. When studies are conducted among specific athlete groups, a higher prevalence of use is found, with 42% using whey protein powders, 29% using protein bars, and 29% using pre-mixed protein drinks [4]. The self-reported prevalence of creatine use among adolescents is around 5%, which is relatively low, considering that it is readily available [16].…”
Section: Introductionmentioning
confidence: 99%
“…Canteen managers were identified as a key stakeholder, but no school managers participated in this research despite being approached. Whitehouse explored perceptions of end users, in this case adolescents, to inform knowledge translation strategies to influence the use of protein supplements in adolescent athletes. Qualitative research methods provide a powerful resource in the dietetic research toolkit, highlighting an area for professional development for dietitians where qualitative methods have been less commonly used.…”
Section: Theory‐guided Knowledge Translation Researchmentioning
confidence: 99%